PENGGUNAAN METODE DESKRIPTIF KUANTITATIF DALAM MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI UJI REGRESI LINIER BERGANDA - Irwanto Irwanto; Fitri Nabila; Ika Sari Dewi; Iswandi Idris; Fajrillah Fajrillah (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
Motivation is a support or a fundamental reason for one's fighting spirit to do something. While the performance is the measure, and or quality of work of people or groups within the organization in carrying out the main tasks. Functions which guided by norms, standard operating rules, criteria and measurements that set or applicable in the organization. This study aims to decide work enthusiasm on employee performance at PT. XYZ in Medan. Data obtained from questionnaires distributed to respondents numbered 14 people using saturated sampling. The research method used is quantitative descriptive. The results of this study note the regression equation of Y = 73,580 + 353X with a positive value that work enthusiasm has a positive effect on employee performance. While the results of the T test can be seen the results of the T table for df = 12 with a level of 10% while the T count obtained from this study showed a value of 4.346. Due to T count> T table = 4.346> 0.1, then Ha accepted and Ho rejected. Thus, the determination test results obtained with the number R2 (R Square) of 0.36 x 100% = 0.36%. Therefore, it can say that the independent variable influences the dependent variable by 0.36% and the remaining 99.64% is influenced by other variables or indicators not examined in this study.